OF EFFECT ADDITIONAL AMOUNT OF DIFFERENT CARRAGEEN ON QUALITY OF LOMEK FISH MEATBALLS (Harpodon nehereues) - Dwi Muarif; Sukirno '; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aims to determine the effect of an additiond different amounts of carrageen to the quality of lomek fish meatballs. The method used was an experiment, with Completely Randomized Design (RAL) word one factor as treatment: B0 treatment: B0 (without carrageen), B1 (carrageen as amount 12.5 g), B2 (carrageen as amount 25 g) and B3 (carrageen as amount 37.5 g). Parameters tested were organoleptic and chemical. The results showed that the best treatment for the quality of lomek fish meatballs is B2 with the amount of carrageen 25 gram, with a creamy white form, compact texture and chewy, the smell of lomek fish meat is lost, and the fish taste is decreasing with the water content value 69, 46, protein 16.16%, fat 8.36%Keywords: Fish lomek, meatballs, number of carrageen